Atypical myelitis in patients with multiple sclerosis: Characterization and comparison with typical multiple sclerosis and neuromyelitis optica spectrum disorders. (February 2021) - Bigaut, K; Lambert, C; Kremer, L; Lebrun, C; Cohen, M; Ciron, J; Bourre, B; Créange, A; Kerschen, P; Montcuquet, A; Carra-Dalliere, C; Ayrignac, X; et al.
Background: Atypical myelitis in multiple sclerosis (MS) is characterized by extensive myelitis in the longitudinal (longitudinally extensive transverse myelitis) or axial plane (transverse myelitis). Objective: To characterize a cohort of MS patients with atypical myelitis. Methods: Atypical myelitis was extracted from the French and Luxembourg MS databases and compared to two cohorts of MS patients with typical myelitis and neuromyelitis optica spectrum disorders (NMOSDs) patients with myelitis. Results: We enrolled 28 MS patients with atypical myelitis, 68 MS patients with typical myelitis and 119 NMOSD patients with a first episode of myelitis. MS patients with atypical myelitis were characterized by a mean age of 34.0 (±10.7) years and 64.3% were women. In 82.1% of the patients, atypical myelitis was the first episode of MS. Mean Expanded Disability Status Scale (EDSS) scores at nadir and 3–6 months after onset were 4.1 ± 2.1 and 3.3 ± 2, respectively. Differences between groups revealed a predominance of cervicothoracic myelitis and a higher level of disability in NMOSD patients. Disability in MS patients with atypical myelitis was more severe than in the MS patients with typical myelitis; 28% had already converted to progressive MS within our mean follow-up of 39.6 (±30.4) months. Conclusion: Atypical myelitis may be the first presentation of MS and is associated with poorer prognosis.